Effect of unilateral, bilateral, and combined plyometric training on explosive and endurance performance of young soccer players - Ramirez-Campillo, R.; Burgos, C. H.; Henriquez-Olguin, C.; Andrade, D. C.; Martinez, C.; Álvarez, C.; Castro-Sepúlveda, M.; Marques, M. C.; Izquierdo, M. (The Journal of Strength and Conditioning Research, 2015)
The aim of the study was to compare the effects of bilateral, unilateral, or combined bilateral and unilateral plyometric training (PT) on muscle power output, endurance, and balance performance adaptations in young soccer players. Four groups of young soccer players (age 11.4 ± 2.2 years) were divided into control group (CG; n = 14), bilateral group (BG; n = 12), unilateral group (UG; n = 16), and bilateral + unilateral group (B + UG; n = 12). Players were measured in unilateral and bilateral countermovement jump with arms, 5 multiple bounds test, 20-cm drop jump reactive strength index, maximal kicking velocity, sprint and agility test time, endurance, and balance performance. The PT was applied during 6 weeks, 2 sessions per week, for a total of 2,160 jumps. After intervention, all PT groups showed a statistically significant (p = 0.05) change in all performance measures, with no statistically significant differences between treatments. Among the 21 performance measures, the B + UG showed a significantly (p = 0.05) higher performance change in 13 of them vs. the CG, whereas the UG and BG showed only 6 and 3, respectively. The current study showed that bilateral, unilateral, and combined bilateral and unilateral PT ensured significant improvement in several muscular power and endurance performance measures in young soccer players. However, the combination of unilateral and bilateral drills seems more advantageous to induce superior performance improvements.